Determinants of Purchase Intention and Purchasing Decisions of Halal Products: The Role of Online Shopping, Taglines, and Social Media Marketing - Eko Budi Satoto (LP2M IAIN Palopo, 2026)
Research aims: This study aims to analyse the influence of online shopping, taglines and social media marketing on purchase intention and purchasing decisions. Design/Methodology/Approach: Statistical analysis was conducted using SEM techniques, with testing performed using Smart PLS version 3.0. Research findings: Digital marketplaces and promotional epithets exert no discernible sway over consumers' acquisitive predispositions, whilst social networking ecosystems demonstrably shape them. Acquisitive predispositions consequentially bear upon procurement comportment; nonetheless, digital marketplaces, promotional epithets, and social networking apparatuses independently yield negligible bearing on such comportment. Acquisitive predispositions intercede between social networking ecosystems and procurement resolutions; contrarily, this intermediary capacity is forfeited when concerning digital marketplaces and promotional epithets. Theoretical Contribution/Originality: The distinctiveness of this enquiry resides in the deployment of acquisitive predisposition as an interceding variable. Practitioners/Policy Implications: This enquiry is anticipated to augment and broaden perspicacity, enlightenment, conceptions, and erudition, particularly concerning the determinants that can sway consumptive acquisitive resolutions. Research Limitations/Implications: The specimen in this enquiry is circumscribed to patrons who possess an Instagram account.